Relationship between Platelet Count and Volume in Patients with Ischemic Stroke - Alfuaadi, Israa H. (Journal of Science in Medicine and Life, 2024)
Background: A prevalent medical condition that results in fatality and long-term impairments is stroke. The abrupt loss of neurologic function associated with a stroke is brought on by a focused disturbance in the blood supply to the brain brought on by ischemia or hemorrhage. Excitotoxicity, oxidative and nitrative stress, inflammation, and apoptosis are a few of the pathophysiological events that contribute to brain injury after stroke. Objectives: Estimate the platelet count and MPV Mean platelet volume in Ischemic Stroke patients and healthy volunteers by using automatic complete blood count and find the linkage between the platelet count and MPV with Ischemic Stroke occurrence. Methodology: Based on 55 samples from patients and a control group, in the period from 13 November 2022 to 8 January 2023 under the supervision of general surgery doctors. Two ml blood sample with EDTA tube was collected from each Patients group with ischemic stroke after clinically diagnosis and Healthy control group, and by using the clinical hematology analyzers CBC to estimate of the PLT count and MPV. Results: In these study. Result show that the mean platelet count of patients group was higher than that of the control group in a highly significant manner (p = 0.002), while the platelet volume of patients group was lower than that of control group in a no significant manner (P= 0.213) . Conclusion: The results of this study emphasize that platelets play a role in the pathogenesis of stroke, PC and MPV appeared to be significantly different from control populations. Ischemic stroke demonstrated significantly higher PC, and revealed significantly lower MPV.